2001
DOI: 10.1046/j.1365-2281.2001.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine responses to 7 days of head‐down bed rest and orthostatic tests in men and women

Abstract: The objective of this study was to investigate plasma volume (PV), total body water, hormones and hydroelectrolyte responses in eight males (25-40 years) and eight females (25-31 years) during 7 days of exposure to simulated microgravity (-6 degrees head-down bed rest, HDBR). Bed rest is a model that has commonly been used to simulate spaceflight. Heart rate (HR), blood pressure (BP) and vasoactive hormone responses were studied before and after HDBR during a 10-min stand test. No change in total body water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 34 publications
3
38
1
Order By: Relevance
“…Alterations in the regulation of the renin-angiotensin system have been reported previously after spaceflight and bed rest. In fact, most bed rest studies have noted an enhancement of PRA (18,33,55), especially in response to an orthostatic challenge (32,33,64). The reasons for the lack of difference in the present study are unknown but may be due to offsetting effects of hindlimb unloading on different aspects of the regulation of plasma renin, including renin release regulated by renal sympathetic nerves (9).…”
Section: Discussionmentioning
confidence: 51%
“…Alterations in the regulation of the renin-angiotensin system have been reported previously after spaceflight and bed rest. In fact, most bed rest studies have noted an enhancement of PRA (18,33,55), especially in response to an orthostatic challenge (32,33,64). The reasons for the lack of difference in the present study are unknown but may be due to offsetting effects of hindlimb unloading on different aspects of the regulation of plasma renin, including renin release regulated by renal sympathetic nerves (9).…”
Section: Discussionmentioning
confidence: 51%
“…But at hour 41, when hormonal measurements were done, all volunteers had normal potassium levels. A biphasic pattern of hormonal activation has been observed in head down tilt, another model used to simulate effects of weightlessness (Nixon et al 1979) that produces a transient increase in plasma aldosterone (Millet et al 2001). After the initial fall of plasma aldosterone with water immersion, a subsequent rise might have caused hypokalemia in two of our divers.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to being a direct vasoconstrictor, angiotensin II increases norepinephrine release from adrenergic nerve terminals and augments the postsynaptic response (29, 30a). Plasma renin activity (PRA) normally increases in response to an orthostatic challenge (12,26,27,41), but this response may be attenuated in some POTS patients (18,21). Jacob et al (18) observed that a subgroup of POTS patients had significantly decreased supine and standing PRA compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%